Effect of aging process on the microstructure, corrosion resistance and mechanical properties of stainless steel AISI 204 - Mohammed Jacob Joseph; Murtadha Abbas Jabbar (Case Studies in Construction Materials, 2019)
In this study, the microstructure thermostability, corrosion resistance, and mechanical properties of AISI204 stainless steel after aging were investigated. The microstructural analysis showed precipitation of M23C6 carbide along grain boundaries and its amount tends to increase with increasing aging time and temperature. Little effect of carbide precipitation on tensile strength where the maximum drop was at temperature 850 °C and aging time 48 h by 5.09%. At the same aging conditions, precipitation severely affected yield strength, ductility, and the microhardness. The yield strength decreased by 46% and microhardness to 210 HV. On the other hand, the ductility increased to 21% in terms of percent reduction in area. Weight loss as a result of uniform corrosion and corrosion current density were strongly dependent on aging time and temperature. Furthermore, Passivation current density showed independent behavior as the temperature increase. Keywords: Stainless steel, Aging, Precipitation, Microstructure, Mechanical, Corrosion